2014
DOI: 10.1080/13548506.2014.931590
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia characterization in a psychosocial approach

Abstract: This study aimed to characterize a group of women diagnosed with fibromyalgia, evaluating the relationship between personality and psychopathology, health status (disability, physical health, mental health, and pain), and potentially traumatic life events (PTLE) before the onset of the syndrome. The disability caused by fibromyalgia, physical and mental health status, pain, PTLE in childhood and in the course of life, and personality were assessed in a sample of 50 women with fibromyalgia, age 25-70 years (M =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…Overall, the findings from the present study showed a particular personality for FM patients and suggested two different clusters in terms of both personality traits and clinical characteristics, as proposed by Gonzalez et al (2015) , confirming the importance of the personality assessment of FM patients ( Malin and Littlejohn, 2012 ).…”
Section: Discussionsupporting
confidence: 83%
“…Overall, the findings from the present study showed a particular personality for FM patients and suggested two different clusters in terms of both personality traits and clinical characteristics, as proposed by Gonzalez et al (2015) , confirming the importance of the personality assessment of FM patients ( Malin and Littlejohn, 2012 ).…”
Section: Discussionsupporting
confidence: 83%
“…Gonzalez et al investigated the association between personal dispositions, previous traumatic events, and psychopathologies and onset of FMS, and found that personal characteristics were very closely linked with FMS, and contrary to common assumptions, previous traumatic events did not exert a strong impact on the onset of the disease [25]. In our study, personal disposition of the women in their chldbearing age was associated with the onset of FMS.…”
Section: Discussioncontrasting
confidence: 58%
“…The personality of patients with FM is more pathological than that of patients with rheumatoid arthritis (RA) and healthy controls [8,14,15]. Other studies have evaluated the personality of FM patients using the Temperament and Character Inventory (TCI), revealing high scores on Self-Transcendence and Harm Avoidance and low scores on Self-Directedness [16,17].…”
Section: Introductionmentioning
confidence: 98%